Healthcare utilisation by children fatally or seriously injured following child maltreatment: analysis of national case series 2005–7 for England. (29th September 2015) - Woodman, J; Brandon, M; Bailey, S; Belderson, P; Gilbert, R
Abstract : Aims: To determine patterns of universal and secondary healthcare use in children seriously or fatally harmed from maltreatment in England Methods: The authors analysed recorded use (and lack of use) of universal and secondary healthcare for children subject to a serious case review (SCR) in England 2005–2007. SCRs occur when a child ≤17 years dies or is seriously harmed, maltreatment is (suspected to be) a factor, and there are lessons for interagency working. Our purposive sample (N=40) was regionally representative and similar (in ethnicity, gender and type of incident) to all SCRs in England 2005–2007 (N=189). The authors used standardised templates and multiple layered readings to extract data from the 40 SCR overview reports. Results: Two-thirds of children were ≤5 years at the time of the incident (toi) (N=26/40) Half (N=20) were boys. Seventy per cent died (N=28/40) and 30% were seriously harmed. Eighty percent of children (N=32/40) were recorded as using/being registered with ≥1 universal care service, of which a third (N=10) had full recorded use of all age-relevant universal care (antenatal care, vaccinations, general practitioner registration, health visitor/midwife/school nurse); 28% (N=9/32) only had recorded contact with a midwife/health visitor/school nurse; and 40% (N=13/32) had missed appointments. Two-thirds (N=25/40) had ≥1 of the following recorded: known chronic conditions (N=16); secondary care follow-up (N=21); admission (N=12). Four out of five families were known to children's social care (CSC) (N=31/40), of whom a third (N=10/31) had no recorded health problems/admissions or secondary healthcare. Six children (15%) were not recorded as known to either CSC or secondary healthcare, of whom three were young babies and two older teenagers. There was much missing data. Conclusion: Primary care services, particularly midwives, health visitors and school nurses, were important for these children but missed appointments were common. Chronic conditions and/or secondary healthcare were common and CSC knew most of these families. SCRs cannot assess unmet healthcare needs because of poor quality data. Data linkage between SCRs and healthcare databases would improve understanding of the contribution of health to the care of children who die or are seriously harmed and would release professional time for reflection about the case.